Integrasi Literasi Digital Islami dalam Pembelajaran PAI untuk Mencegah Dampak Negatif Media Sosial pada Generasi Z - Resti Yulastri; Putri Ramadhon; Defriani Defriani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the integration of Islamic digital literacy into Islamic Religious Education (PAI) as a preventive effort against the negative impacts of social media on Generation Z. The background of this research arises from the increasing dependence of Gen Z on digital platforms, which significantly influences their religious understanding, behavior, and character development. The study aims to identify the level of students’ digital literacy, explore how PAI teachers integrate Islamic values into digital learning activities, and analyze the implications of this integration for students’ online behavior. Using a sequential explanatory mixed-methods design, quantitative data were collected through Likert-scale questionnaires, followed by qualitative data obtained from interviews and documentation. The findings reveal that Gen Z demonstrates high social media engagement but limited critical abilities in verifying online religious information, making them vulnerable to misinformation, moral degradation, and unhealthy digital habits. However, when PAI instruction incorporates Islamic digital literacy—such as tabayyun, ethical communication, and value-based content analysis—students show improved critical thinking, ethical awareness, and responsible social media use. The study concludes that integrating Islamic digital literacy into PAI provides a strategic educational framework to strengthen students' digital ethics, enhance their resilience against harmful online content, and promote a balanced, value-driven engagement with digital media.